Feasibility, acceptability, and effectiveness of group antenatal care on the continuum of care and perinatal outcomes in Sub-Saharan Africa: A systematic review and meta-analysis protocol - Meresa Berwo Mengesha; Tesfaye Temesgen Chekole; Hiluf Ebuy Abraha; Etsay Weldekidan Tsegay; Abadi Hailay Atsbaha; Mihretab Gebreslassie; Zenawi Hagos Gufue (PLoS ONE, 2025)
Introduction Women with adequate antenatal care (ANC) experience more reduction in adverse maternal and perinatal outcomes compared to those with insufficient care. However, the conventional individualized ANC models have not significantly improved perinatal outcomes. Comprehensive, woman-centered group ANC (G-ANC) interventions, integrating medical care with education, demonstrate positive effects on maternal and newborn health. While promising evidence exists in sub-Saharan Africa, the feasibility, acceptability, and effectiveness of G-ANC in resource-limited settings require further investigation. The variability in current studies further indicated the need for meta-analyses and systematic reviews to consolidate findings and clarify the overall effectiveness of G-ANC interventions. This synthesis aims to provide comprehensive evidence supporting the implementation of group prenatal care models in low-resource settings. Ultimately, it seeks to establish robust evidence to guide policy and practice, contributing to reduced maternal and perinatal mortality in the region. Methods and analysis This systematic review and meta-analysis protocol adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols guidelines. A comprehensive literature search will be conducted across multiple electronic databases, including PubMed/MEDLINE, Web of Science, EMBASE, and CINHAL, to identify pertinent articles published from January 1, 2016, to June 30, 2024. Experimental studies (pre-post, quasi-experimental study, cluster randomized controlled trial), prospective cohort design, prospective comparative study, and qualitative and mixed method designs will be included in the review. The Abstract and full-text screening will be conducted by three reviewers using Covidence, according to the eligibility criteria set. The Joanna Briggs Institute (JBI) Critical Appraisal Tools, specifically designed for JBI Systematic Reviews, will be utilized to assess the methodological quality of the included studies. Statistical heterogeneity will be assessed using the Higgins test. Meta-analysis will be conducted using R statistical software version 4.4.2, which will implement random effects models to determine the weights. Pre-specified subgroup analysis and sensitivity analysis will be performed as needed. The study results will be reported in order, starting with primary outcomes and then secondary outcomes and important subgroup outcomes analyses. Ethics and dissemination Ethical approval is not applicable as no original data will be collected. The findings of this review will be disseminated through publication and conference presentations. PROSPERO registration number CRD42024565501